The Potential of the Green Token Economy in Promoting Sustainable Investment in Indonesia - Kamaludin (Nomico, 2026)
The transition toward sustainable development has intensified the demand for innovative green financing instruments capable of mobilizing investment while ensuring transparency and accountability. In this context, the green token economy has emerged as a digital finance innovation enabled by blockchain technology, offering new opportunities for sustainable investment. This study examines the potential of the green token economy in promoting sustainable investment in Indonesia through a qualitative descriptive–analytical approach with a normative–policy perspective. The analysis is based on regulatory documents, policy frameworks, and academic literature on sustainable finance, blockchain, and digital assets. The findings indicate that green tokens possess significant potential to enhance inclusivity, traceability, and efficiency in financing renewable energy and environmentally sustainable projects. By tokenizing green assets, this model enables broader investor participation and improves transparency in the allocation and monitoring of funds. However, the study also reveals substantial normative and policy challenges, including regulatory fragmentation, legal uncertainty, risks of greenwashing, and insufficient investor protection mechanisms. These constraints limit the institutional legitimacy and scalability of green tokens within Indonesia’s financial system. The study concludes that the green token economy can contribute meaningfully to sustainable investment only if supported by an integrated and adaptive regulatory framework. Aligning digital asset regulation with sustainable finance principles and environmental governance is essential to ensure that green tokens function as credible instruments for long-term sustainable development rather than speculative digital assets.